Development Of Digital Reporting System Using Whatsapp Chatbot Alert E-Pol (Police Service Frontline Integration System) To Accelerate Police Response To Public Complaints (Open Society Conference, 2025)
In today’s digital era, the need for a fast and efficient reporting system is increasing, especially for the police who must immediately respond to public complaints. WhatsApp, as a popular instant messaging application, offers a potential platform to develop a digital reporting system that is accessible to the wider public. This research aims to develop and test the effectiveness of a digital reporting system using WhatsApp chatbot in accelerating police responses to public complaints. This research method includes the stages of needs analysis, system design, implementation, and evaluation. Data was collected through surveys and interviews with potential users as well as testing the system in a police environment. Data analysis is carried out qualitatively and quantitatively to evaluate user performance and satisfaction with the developed system. The results of the study show that the digital reporting system using the WhatsApp chatbot is able to increase the speed of police response to public complaints. This result was obtained based on a validation test with a score of 91% of the very valid category by both media technology experts and a practicality questionnaire of 90.6% of the very practical category. Users report a high level of satisfaction with the ease of use and speed of response of the system.